Effects of inclination angle on conduction-natural convection in divided enclosures filled with different fluids - Varol, Yasin; Öztop, Hakan Fehmi; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2010)
Laminar natural convection in inclined enclosures filled with different fluids was studied by a numerical method. The enclosure was divided by a solid impermeable divider. One side of partition of enclosure was filled with air and the other side had water. The enclosure was heated from one vertical wall and cooled from the other while horizontal walls were adiabatic. The governing equations which were written in stream function-vorticity form were solved using a finite difference technique. Results were presented by streamlines, isotherms, mean and local Nusselt numbers for different thermal conductivity ratios of solid impermeable material (plywood or concrete), inclination angle (0 degrees <=phi <= 360 degrees) and Grashof numbers (10(3)<= Gr <= 10(6)). The code was validated by earlier studies, which are available in the literature on conjugate natural convection heat transfer. Analytical solutions were obtained for low Grashof numbers. Obtained results showed that both heat transfer and flow strength strongly depended on thermal conductivity ratio of the solid material of partition, inclination angle and Grashof numbers. The heat transfer was lower in the air side of the enclosure than that of the water side. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Conjugate; Partition; Enclosure; Different fluids